The Effect of Puzzles on the Cognitive Development of Children Aged 5–6 Years - Nur Isnaini Khosyati; Baik Nilawati Astini; Gunawan Gunawan (Indonesian Journal of Elementary and Childhood Education, 2026)
This study aims to determine the effect of educational puzzles on the cognitive development of children aged 5–6 years at As-Syafa'ah Early Childhood Education (ECE). The research was prompted by the limited use of innovative learning media, which has hindered children's cognitive growth, particularly in problem-solving, logical thinking, and symbolic reasoning. A quantitative pre-experimental approach was adopted, employing a one-group pretest-posttest design with a sample of 16 children aged 5–6 years. Data were collected through structured observation checklists and documentation, then analyzed using the Shapiro-Wilk normality test and a paired-sample t-test via IBM SPSS Statistics 30. The results showed a significant increase in the mean score from 48.68 in the pretest to 78.87 in the posttest following the puzzle intervention (t=31.086, p < .001). Consequently, the null hypothesis was rejected, indicating that educational puzzles significantly enhance the cognitive development of children aged 5–6 years at As-Syafa'ah ECE. Puzzles effectively stimulated logical thinking, problem-solving abilities, and pattern-symbol recognition, proving to be an engaging and effective pedagogical tool in early childhood education.